DESIGN AND CONSTRUCT OF THE SAJOR-CAJU MUSHROOM SHREDDING MACHINE PROTOTYPE - Sumrit, Thawanrat; Deeli, Natthawut; Inrirai, Patcharaporn (Life Sciences and Environment Journal, 2022)
This research aims to design and construct the sajor-caju mushroom shredding machine prototype and transfer technologies to community enterprises. The machine was made from stainless steel and consisted of a set of machine structures, a blade set, and a feed hopper with a controlling motor system of 0.5 HP. The operating principle is based on automatic blade rotation. The machine has the maximum load of 1,000 grams of the mushroom. The comparison study was conducted between the manual labor process and the machine prototype using fresh sajor-caju mushroom samples of 1,000 grams per time. The two methods were tested for three repetitions. The result showed that the machine prototype at the blade speed of 250 rpm could reduce the average standard time to 6.81 minutes compared to 25.53 minutes of the manual labor process. Furthermore, the average cutting rate of whole mushrooms is 7.87 kilogram per hour compared to 2.11 kilogram per hour of the labor process. Therefore, this machine runs four times faster than the manual labor. The physical characteristics of the mushroom from these two methods were found to be similar. Economic value analysis revealed that using this machine the payback period will be 0.25 years or 3 months.